TRAINING FOR DESIGNING SCIENTIFIC WRITING TO THE TEACHERS OF MADRASAH TSANAWIYAH (MTS) GALESONG SELATAN TAKALAR - Munir; Abdullah; La Sunra; Hasriani G (Jurnal Gembira: Pengabdian Kepada Masyarakat, 2023)
This activity aims to improve the ability, knowledge and skills for the teachers of Madrasah Tsanawiayah Galesong Selatan Takalar in writing or compiling scientific works in the form of writing Articles or papers. This activity was carried out for one week using the lecture method, question and answer, discussion, practice in compiling scientific writing, such as articles and paper. At the end of this activity, an evaluation was held by the Team as a part to determine the success of the participants in this activity. The results of the evaluation of this activity showed that 80% of the participants succeeded in wring articles and paper for Journal (national or international) . In other words, there is an increase in the knowledge and skills as well as high motivation of the participants in designing article or paper. Thus, it can be concluded that this activity has been successful.